The Concordat with Serbia of 1914 as a Forebearer of Modern Concordats and the Model of Church-State Cooperation - Rakitić, Dušan (NBP. Nauka, bezbednosti, policija, 2022)
The concordat of 1914 affirmed the Kingdom of Serbia, on the eve of the Great War, as the state with sufficient legal and political capacity to secure equal treatment for its newly acquired Catholic minority population in relation to the Orthodox majority, and, consequently, to serve as the pivot of unification of South Slavs irrespective of their religious affiliation. The aim of the paper examine the claim that the subject concordat represented the model for the new generation of concordats which came into being after the World War I. If that hypothesis proves true, the significance of the subject concordat should be assessed against the backdrop of two facts – the key features of the interwar concordats have continued to permeate the concordats that have been concluded since World War II until the present day, as well as that the subject conceptual approach to concordats, as agreements of two equal counterparties on issues of common interest, made way to the model of Church-state cooperation, which is pervasive in modern-day Europe. The conclusion may further magnify the seminal nature of the concordat concluded with the Kingdom of Serbia in 1914, and, consequently, of its own ancient and rudimentary predecessor, the concordat with the Principality of Montenegro of 1886.
Keywords: Concordat; Kingdom of Serbia; Church-state cooperation; Roman-Catholic Church